Pengaruh Kemudahan Penggunaan Dan Persepsi Manfaat Aplikasi Jd.Id Terhadap Keputusan Pembelian Pada Mahasiswa (Studi Kasus Pada Mahasiswa Jurusan Manajemen FEB UNISMA Malang) - Anital Umroh; N. Rachma; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study examines the effect of ease of use and perceived benefits of the JD.id application on student purchasing decisions. There are several new trends that emerged when the internet and technology began to enter Indonesia, including shopping trends that are now starting to change, namely online shopping, one of which is using JD.Id. Some inconvenience issues with JD.id. when accessing the application, there are still many who say that using the JD.id application is still difficult, such as access failure, unable to check out etc. In addition, the Customer Service service is not responsive enough, the wrong item is sent, to the unilateral cancellation of transactions by the system. This causes lower decision making. This study uses an explanatory with a quantitative approach. Determination of the number of samples using the formula from Malhotra as many as 72 respondents using multiple linear regression analysis. The results showed that the ease of use and perceived benefits of the JD.id application simultaneously influenced student purchasing decisions and partially ease of use had a significant effect on purchasing decisions. Perceived benefits have a significant effect on purchasing decisions. Keyword : Ease of Use, Perception of the Benefits of the JD.Id Application, Decisions  Purchase